Exploring the Impact of Self-Esteem and School Climate on Assertive Behavior in Bullying Victims: A Scoping Review - Djatmiko, Grace Putri; Sampe Tondok, Marselius (Bulletin of Counseling and Psychotherapy, 2025)
Assertive behavior plays a crucial role for bullying victims in authentically expressing themselves and maintaining self-respect, while a positive school climate fosters identity development and reduces bullying. This study aims to examine the relationships between self-esteem, school climate, and assertive behavior in adolescents. The research employs a systematic literature review with a scoping review approach based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Sources include journal articles and books published within the last ten years, retrieved from databases such as Google Scholar, Semantic Scholar, ScienceDirect, and Wiley Online Library. Analysis of 30 sources reveals that self-esteem influences assertive behavior, while a research gap exists regarding the correlation between school climate and assertive behavior in adolescents. This study holds significance for adolescents and schools in reducing bullying by emphasizing the role of both personal and contextual factors.